2021
DOI: 10.1007/s10549-021-06453-8
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and menopausal status impact the features and molecular phenotype of invasive lobular breast cancer

Abstract: Purpose We investigated the relationship between obesity, menopausal status, and invasive lobular carcinoma (ILC), the second most common histological subtype of breast cancer. Specifically, we evaluated the association between body mass index (BMI), metabolic syndrome, the 21-gene Oncotype Recurrence Score (Oncotype RS), and pathological features in patients with hormone receptor (HR)-positive, human epidermal growth factor receptor-2-negative ILC. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…A metaanalysis examined data from multiple investigations involving 1,951 cancer patients and 2,295 healthy controls revealed that retn polymorphism significantly raised the risk of cancer (OR = 1.23). Classification of cancer type indicated that the rs1862513 variation significantly increased the incidence of breast cancer in Caucasians (OR = 1.22, CG+GG vs. CC; OR = 1.18, G vs. C) while, another data showed no correlation between the retn polymorphisms and cancer risk (14).…”
Section: Discussionmentioning
confidence: 94%
“…A metaanalysis examined data from multiple investigations involving 1,951 cancer patients and 2,295 healthy controls revealed that retn polymorphism significantly raised the risk of cancer (OR = 1.23). Classification of cancer type indicated that the rs1862513 variation significantly increased the incidence of breast cancer in Caucasians (OR = 1.22, CG+GG vs. CC; OR = 1.18, G vs. C) while, another data showed no correlation between the retn polymorphisms and cancer risk (14).…”
Section: Discussionmentioning
confidence: 94%
“…The underlying reason for this outcome disparity appears to be multifactorial. Those with the highest ADI had more hormone-receptor (HR) positive disease and elevated BMI, which together have been linked to worse outcomes in prior studies ( 16, 17, 19, 22, 23 ). In a multivariable model, the association between elevated ADI and worse EFS was no longer significant when adjusting for other factors, including the presence of overweight/obese BMI.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, in nearly all ADI quintiles having obese/overweight BMI was associated with worse EFS except for ADI quintile 1 in a test of interaction. Although the mechanisms through which obesity mediates ILC proliferation remain incompletely understood, ILC is known to express estrogen receptor and obesity is linked with states of increased estrogen due to peripheral production in adipose tissue ( 16, 24, 25 ). These suggest that high estrogen states, including the use of hormone replacement therapy, drive the growth of ILC beyond that of other histological subtypes, such as the more common IDC ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that high BMI is associated with low RS in women who are postmenopausal. 16 , 19 In addition, researchers interpreted this correlation based on the theory that enriched adipocytes in women who are obese increase the plasma levels of estradiol and progesterone, 24 , 25 which may curtail the RS by promoting ER and PgR expression in tumors. By contrast, our findings showed an association between high BMI and RS in younger women who were premenopausal.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, the proliferation module of RS could be upregulated by the obesity-related inflammation; it remains unclear whether the RS in women with a high BMI is lower or higher than in those with a normal BMI. A previous study showed that a higher BMI was associated with a lower RS in women who were postmenopausal with invasive lobular cancer, which is a principally hormone-driven cancer . A study by Pomponio et al suggested that the tumors of women who are postmenopausal with a higher BMI generally have a lower RS, whereas another study reported that the association of BMI with RS interacts with menopausal status, even though patients who are obese are more likely to have an RS less than 11 compared with that of women who are not overweight …”
Section: Introductionmentioning
confidence: 99%